Evaluation The Implementation of Media Center in Bekasi City (Evaluasi Implementasi Media Center di Kota Bekasi) - Andriariza, Yan (Jurnal Pekommas, 2016)
Information about government, often not directly reported by the government, this makes the information concerns do not correspond to reality. Therefore government establish a media center in every government agency. Unfortunately not all of the media center active in sending information, but ideally the whole media center actively sending news. This study will evaluate the implementation of the media center in Bekasi. The evaluation is based on 10 variables, that are Access, Coverage, Frequency, Refraction, Size and Purpose of the program, Resources, Characteristics and Attitudes of implementator, Communication between the organization and implementing activities, and environmental conditions. The results of the evaluation of the Media Center in Bekasi was already have a good access, coverage is enough to reach some levels of society, although there is a Refraction because most visitors are reporters. Based on visitor frequency and delivery of news, the condition has increased. Comparison between the function and implementation, media center in Bekasi has carried out the functions set out in the General Guidelines for Media Center well. Resources owned has been quite good, although the terms characteristic of implementator are still not optimal. But the attitude of the implementator and the environment is very favorable to media center in Bekasi. Coordination with related agencies also goes well.Informasi dan data mengenai pemerintahan, seringnya tidak secara langsung disampaikan oleh pemerintah, hal ini membuat kekhawatiran informasi yang ada tidak sesuai dengan kenyataannya. Karenanya pemerintah membentuk media center di setiap lembaga pemerintahan. Sayangnya belum semua media center aktif dalam mengirimkan informasi, padahal idealnya seluruh media center aktif mengirimkan berita. Maka melalui penelitian ini akan mengevaluasi implementasi media center khususnya di Kota Bekasi. Evaluasi tersebut dilihat dari 10 variabel, yaitu akses, cakupan, frekuensi, bias, ukuran dan tujuan program, sumber daya, karaketristik dan sikap pelaksana, komunikasi antar organisasi dan aktivitas pelaksana, dan kondisi lingkungan. Hasil dari evaluasi terhadap Media Center Kota Bekasi antara lain akses yang sudah baik, cakupan yang sudah cukup menjangkau beberapa lapisan masyarakat, walau ada sedikit bias karena sebagian besar pengunjung wartawan. Berdasarkan frekuensi pengunjung dan pengiriman berita, kondisinya semakin mengalami peningkatan. Perbandingan antara fungsi dan implementasinya terlihat Media Center Kota Bekasi telah melaksanakan fungsi yang tertuang dalam pedoman umum media center dengan baik. Sumber Daya yang dimiliki telah mumpuni, walaupun dari segi karaketristik pengelolanya masih belum optimal. Tetapi sikap pengelola dan lingkungan sangat mendukung keberlangsungan media center Kota Bekasi. Koordinasi dengan instansi terkait juga berjalan dengan baik.